Thermodynamic properties of ErВ4 - Morozov Anton (E3S Web of Conferences)
The temperature dependence of the molar heat capacity of erbium tetraboride in the range 2-300 K has been experimentally studied. Anomalies were found on the temperature dependence of the heat capacity due to the processes of transition to antiferromagnetic state at ТN=15.2 K. Using the received data of temperature dependence of heat capacity, temperature changes of magnetic, lattice, electronic and Schottky contributions to the heat capacity of ErB4 have been determined and analyzed. The lattice contribution to the heat capacity of erbium tetraboride was calculated by the correspondence method by comparison with the lattice heat capacity of LuB4; the temperature dependence of the excess component of the heat capacity Δc(T) was obtained by subtracting the lattice and electron contributions from the total heat capacity. In our opinion, the value of Δc(T) together with the magnetic contribution contains one more component - the Schottky contribution to the heat capacity. The temperature dependences of the magnetic component and the Schottky contribution to the heat capacity extracted from the total heat capacity allowed us to determine the value of the exchange integral J (or the exchange parameter J/k).